Kesan Pendekatan Kecerdasan Pelbagai Secara Atas Talian Terhadap Literasi Digital, Pembelajaran Terarah Kendiri Dan Pencapaian Pelajar Dalam Kalangan Pelajar Tingkatan Empat Bagi Topik Daya Dan Gerakan - Ahamad, Adri Nirwan (2020)
This study aimed to examine the effect of Online Multiple Intelligence Based Approach (eKP-TKP) on digital literacy, self-directed learning and achievement in Force and Motion of Form Four Science students. This study applied a quasi-experimental method with “A Design Group Pre Test- Post Test” design. The sample consisted of 30 Form Four students who received eKP-TKP treatment. The same group acted as the experimental group. The impact of eKP-TKP on three variables which is digital literacy, self-directed learning and achievement in Force and Motion were measured three times through a pre-test, post-test and post test extension. ANOVA with Repeated Measurement were used for quantitative data analysis. Findings indicate that the use of eKP-TKP was found to have significant impact in improving digital literacy, self-directed learning and achievement in Force and Motion. Extension analysis using non-parametric Friedman and Wilcoxon analysis indicate that only Logic Mathematic, Musical, Visual and Interpersonal intelligence have significant impact on Digital Literacy and only Logic Mathematic, Visual Spatial and Interpersonal intelligence have significant impact on Self-directed learning while only Logic Mathematic, Interpersonal and Intrapersonal intelligence have significant impact in achievement of Force and Motion. This study suggests that eKP-TKP is suitable to be implemented because it can stimulate multiple intelligences in the student simultaneously thus enhancing understanding during learning.